PEMANFAATAN KOMUNIKASI BLUETOOTH UNTUK BUKA TUTUP GORDEN - , MIFTAKHUL KUSUMA ALFI FAUZI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Utilization of Bluetooth Communication to open and close curtains is a tool that is made to open and close the curtains via bluetooth communication which can be controlled through an Android phone so as to facilitate control curtains. This tool consists of two parts which consist of mechanical systems and electronic systems. Mechanical systems including DC motors, chassis, curtain rail, timing belt. For electronic systems including the minimum system, bluetooth module, H-Bridge Driver, and software programs. The workings of this tool is the bluetooth module will take orders from an Android phone, then the data will be processed and forwarded to control a DC motor that will drive the curtains open and close, while the limit switch is used to turn off the motor when the curtain has reached the fully open or closed.